AN ANALYSIS OF STUDENTS’ RECOUNT TEXT WRITING ABILITY AT SMK TELKOM 2 MEDAN - Putri Sundari Hutabarat; Natalia W.P. Tarigan; Julia Tesalonika Br Hia; Elvira Rosyida M.R. (Jurnal Basataka (JBT), 2024)
This study aims to analyze the ability to write recount texts in English for grade 10th students at SMK Telkom 2 Medan. Using a descriptive qualitative approach, this research focuses on four main aspects in writing assessment, namely structure, grammar, vocabulary, and cohesion. Data were collected through writing tests, classroom observations, and questionnaires involving 22 students. The results showed that the students' overall writing ability was in the “good” category with an average score of 79.3. The structure aspect was the most mastered aspect, as most students were able to apply the recount text organization correctly. The use of vocabulary was also quite good, although some students still showed a limited variety of words. However, the grammar aspect was the main weakness, where many students had difficulty in using tenses and sentence construction. The cohesion aspect was moderately mastered, although there were still some students who lacked fluency in connecting ideas between sentences. The study concludes that although students performed well in the structure and vocabulary aspects, further learning emphasis is needed on the grammar and cohesion aspects to improve the overall quality of writing.